2023
DOI: 10.3390/birds5010001
|View full text |Cite
|
Sign up to set email alerts
|

Predator-Proofing Avian Nestboxes: A Review of Interventions, Opportunities, and Challenges

Joseph Marcus,
Adam Hart,
Anne Goodenough

Abstract: Nestboxes are commonly used to increase the number and quality of nest sites available to birds that usually use tree cavities and are considered an important conservation intervention. Although usually safer than natural cavities, birds nesting in simple, unmodified wooden nestboxes remain at risk of depredation. Accordingly, numerous design and placement modifications have been developed to ‘predator-proof’ nestboxes. These include: (1) adding metal plates around entrance holes to prevent enlargement; (2) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 138 publications
0
0
0
Order By: Relevance
“…Many nest-box studies predicted higher breeding success in larger rather than in smaller boxes when increased nest-building efforts associated with the occupation of larger nest chambers would better reflect aspects of the quality of the nest-builders, their mates, or their territories [4,44,63,82,89,[143][144][145][146][147]. Previous studies in contrasting habitats throughout Europe also showed that Great Tits or other cavity-nesting passerines occupied more often the larger chamber when there was an option to choose between at least two chamber sizes.…”
Section: Nest-size Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many nest-box studies predicted higher breeding success in larger rather than in smaller boxes when increased nest-building efforts associated with the occupation of larger nest chambers would better reflect aspects of the quality of the nest-builders, their mates, or their territories [4,44,63,82,89,[143][144][145][146][147]. Previous studies in contrasting habitats throughout Europe also showed that Great Tits or other cavity-nesting passerines occupied more often the larger chamber when there was an option to choose between at least two chamber sizes.…”
Section: Nest-size Componentsmentioning
confidence: 99%
“…Use of nest-boxes also facilitates experiments in humancontrolled environments to reveal more easily the underlying proximate mechanisms that link the individual responses to environmental change. The costs and benefits of nest-box use have been reviewed recently by Thompson et al [42], Zhang et al [43], and Marcus et al [44].…”
Section: Introductionmentioning
confidence: 99%